THE METHODOLOGICAL FUNCTION OF PHILOSOPHY IN A SCIENTIFIC DEPICTION OF THE WORLD - EFENDIYEV, F.M; DASHDAMIROVA, C.F (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
Science is first and foremost a system of knowledge that has been created in the process of historical development. This system of knowledge is logically ordered and constantly updated in the course of social practice. Science arises on the basis of the productive and practical activities of the workforce and at each stage of history it reflects the level of reached awareness of the laws of nature and society. The engine of science, scientific development, is neither speculative reasoning nor the logical and deductive development of a theory, but it is primarily the necessity for the development of material production, technology. The logic of the development of science is determined by the productive and practical activities of people, the development of methods of thinking, the level of experimentation. In this process physical-philosophical, biological-philosophical, historical-philosophical theoretical principles are synthesized, on which private-scientific fundamental principles are based. This is how, for example, the deductive connection between the philosophical concept of the conservation of matter and motion and the scientific principle of conservation of energy is realized between the philosophical idea of discontinuity, the presence of jumps in nature and the hypothesis of quantization between the concept of struggle and unity of opposites and the idea of complementarity, corpuscular - wave dualism. The combination of philosophical knowledge with specific natural science knowledge forms the presentation of the scientific picture of the world. This article attempts to characterize and analyze these facts and to show the role of the methodological function of philosophy in the development of the scientific picture of the world.